A Survey on Understanding the Perception and Awareness Towards a Circular Economy: A Comparative Study Between Nepal and the USA - Sugam Upadhayay; Omaima Alqassimi (Westcliff University, 2019)
This article offers a comparative analysis of the perception and awareness people have concerning the circular economy (CE) in Nepal and the United States of America (USA). The survey in the form of online questionnaires were distributed through convenience sampling and data was collected from 29 respondents in Nepal and 25 in the USA. The results indicate that, across the sampled countries, though respondents were highly concerned about the environment and resources utilization, their perception and understanding of CE principals and its applicability were limited to the concept of reuse, recycle and remanufacture (3R). Similarly, organizational involvement in CE activities were found to be significantly low in both countries, indicating no structural or operational level support such as creating job positions for CE officers. Additionally, the practice of publishing sustainability and circularity reports to enable the CE were not found during the data analysis procedure. In comparison to Nepal, USA respondents picked inter and intra organizational collaboration and cooperation along with research and development (R&D) as an important enabler of CE. Finally, policy level interventions through mandatory and voluntary regulations, subsidization of CE activities and involvement of governmental and non-governmental agencies were recommended in creating a positive perception and awareness of CE.